Relationship between income inequality and residential segregation of socioeconomic groups. Issue 4 (2nd April 2020) - Tammaru, Tiit; Marcin´czak, Szymon; Aunap, Raivo; van Ham, Maarten; Janssen, Heleen
ABSTRACT: This paper provides new insights into the relationships between income inequality and residential segregation between socioeconomic groups by undertaking a comparative study of European urban regions. In Europe, income inequalities are the lowest in North Europe and the highest in South Europe. In many East European countries, a switch from low inequality to high inequality has taken place. The main findings show that changes in the levels of residential segregation between socioeconomic groups correlate to changes in the levels of income inequality found approximately 10 years earlier, that is, with a time lag.